Lithium decreases the effects of neuronal calcium sensor protein 1 in pedunculopontine neurons. Issue 6 (31st March 2016) - D'Onofrio, Stasia; Urbano, Francisco J.; Messias, Erick; Garcia‐Rill, Edgar
Abstract: Human postmortem studies reported increased expression of neuronal calcium sensor protein 1 (NCS‐1) in the brains of some bipolar disorder patients, and reduced or aberrant gamma band activity is present in the same disorder. Bipolar disorder is characterized by sleep dysregulation, suggesting a role for the reticular activating system (RAS). Lithium (Li + ) has been shown to effectively treat the mood disturbances in bipolar disorder patients and was proposed to act by inhibiting the interaction between NCS‐1 and inositol 1, 4, 5‐triphosphate receptor protein (InsP3 R). NCS‐1 is known to enhance the activity of InsP3 R, and of Ca 2+ ‐mediated gamma oscillatory activity in the pedunculopontine nucleus (PPN), part of the RAS. This study aimed to determine the nature of some of the intracellular mechanisms of Li + on rat PPN cells and to identify the interaction between Li + and NCS‐1. Since Li + has been shown to act by inhibiting the enhancing effects of NCS‐1, we tested the hypothesis that Li + would reduced the effects of overexpression of NCS‐1 and prevent the downregulation of gamma band activity. Li + decreased gamma oscillation frequency and amplitude by downregulating Ca 2+ channel activity, whereas NCS‐1 reduced the effect of Li + on Ca 2+ currents. These effects were mediated by a G‐protein overinhibition of Ca 2+ currents. These results suggest that Li + affected intracellular pathways involving the activation of voltage‐gated Ca 2+ channels mediated by an intracellular mechanism involving voltage‐dependent activation of G proteins, thereby normalizing gamma band oscillations mediated by P/Q‐type calcium channels modulated by NCS‐1. Abstract : The article describes novel findings, not being considered for publication elsewhere, showing that lithium downregulates the action of neuronal calcium sensor protein 1 (NCS‐1), which is overexpressed in bipolar disorder patients. Because NCS‐1 promotes gamma band activity at low concentrations but blocks it at high concentrations, overexpression would suppress gamma band activity, as has been observed in this disorder. These findings provide a physiological mechanism for the palliative effects of lithium.